Differences between winning and losing teams football match type function by studying performance indicators - Gómez Ruano, Miguel Ángel; Gómez, M.; Jiménez, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The aim of the present study was to identify the performance indicators that best discriminated between winning and losing teams in elite balanced and unbalanced football maches. The analysis was based on 64 matches played during the World Cup tournaments held in Germany 2006. The performance indicators gathered were: actions inside the goal area, shots off goal, shots on goal, effectiveness, crosses, offsides, corners, crosses to the goal area, fouls committed, penalties, yellow and red cards, turnovers, steals, saves. The discriminant analysis of these matches showed that: the variables that best discriminated the winning and losing teams in balanced games were the actions inside the goal area, the crosses to the goal area and corners against; and the variable that best discriminated the winning and losing teams in unbalanced games was the crosses to the goal area. These results suggest that game type affects the teams’ performance and consequently the game styles. This information may be useful to both coaches and performance analysts, increasing the knowledge about football performance indicators and allow to improve the training process.